Prevention and treatment of venous thromboembolic disease. Issue 7 (18th July 2018) - McNeill, Susan; Bagot, Catherine
Abstract : Awareness of the risk factors for venous thromboembolic (VTE) disease and timely administration of thromboprophylaxis can prevent many VTE events. This article examines these risk factors and the recommended strategies to prevent VTE, as well as discussing the diagnosis and treatment of an event that has already occurred.